Neural Antecedents of Emotional Disorders: A Functional Magnetic Resonance Imaging Study of Subsyndromal Emotional Symptoms in Adolescent Girls - Das, Pritha; Coulston, Carissa M.; Bargh, Danielle M.; Tanious, Michelle; Luan Phan, K.; Calhoun, Vince D.; Malhi, Gin S. (Biological psychiatry (1969), 2013)
Emotional symptoms (ES) emerge forme fruste in adolescence, before manifesting as fully fledged emotional disorders. Studies indicate that subsyndromal ES precede the onset of emotional disorders. We hypothesized that adolescents showing subsyndromal ES will show perturbations in the emotion regulatory frontolimbic network (FLN) during emotion processing. Fifty-eight female adolescents underwent functional magnetic resonance imaging while viewing an image-based emotion-processing task. Within this sample, 33 (56.9%) displayed emotional symptoms and 25 (43.1%) did not. Clinical measures, including assessments of mood and anxiety, were administered and participants were allocated to one of two groups based on the presence (ES+) or absence (ES−) of subsyndromal ES. Group comparisons were used to identify differential patterns of neural engagement and their relationship to clinical variables. Groups displayed emotion-specific differences in FLN activity with increased frontal activity in ES+ girls during positive emotion processing and decreased frontal and limbic activity during negative emotion processing. Trait anxiety was the strongest clinical predictor of group membership (ES+ versus ES−) and displayed a significant negative correlation with hippocampal neural activity during negative emotion processing. In addition, between the groups, the hippocampus displayed a pattern of reverse coupling with the amygdala and insula that was also significantly correlated with trait anxiety. There is divergence in the pattern of FLN neural processing in adolescent female subjects determined by emotional symptoms. Future research is needed to corroborate these findings and to underline their implications longitudinally.